Beneficial Effects and Toxicity Studies of Xian-ling-gu-bao on Bone Metabolism in Ovariectomized Rats - Wu, Hao; Zhong, Qingxiang; Wang, Jing; Wang, Man; Fang, Fang; Xia, Zhi; Zhong, Rongling; Huang, Houcai; Ke, Zhongcheng; Wei, Yingjie; Feng, Liang; Shi, Ziqi; et al. (Frontiers in Pharmacology, 2017)
Xian-ling-gu-bao (XLGB) is a well-known patented traditional Chinese prescription widely used to treat osteoporosis, osteoarthritis, aseptic bone necrosis, or climacteric syndrome. However, recent reports have suggested that XLGB may cause liver injury in humans. In the present study, we aimed to evaluate the efficacy of XLGB in the prevention of osteoporosis in the zebrafish and ovariectomized (OVX) rats, both of which have been used as osteoporosis models. The safety of XLGB after long-term administration to OVX rats was also assessed. OVX rats were administered by oral gavage 270 mg/kg (recommended daily dose), 1350 mg/kg, and 1800 mg/kg of XLGB for 26 weeks. Bone mineral density (BMD), relative bone surface to bone volume (BS/BV), relative bone volume to total volume (BV/TV), trabecular number (Tb.N), mean trabecular thickness (Tb/Th), and mean trabecular spacing (Tb.Sp) in OVX rats were examined at the end of the 26-week dosing period. Additionally, OPG and RANKL expression in the femur were determined by western blot and immunohistochemical staining. To evaluate the safety of XLGB, body weight, hematology, serum biochemistry markers related to toxicology, and organ histopathology were determined in each group of OVX rats. Conversely, the zebrafish was treated with prednisolone to induce osteoporosis in the embryo. Disodium etidronate was used as a treatment control. XLGB was shown to be effective in preventing osteoporosis in both the OVX rats and the prednisolone-treated zebrafish. Similarly, XLGB increased OPG protein and decreased RANKL protein in OVX rats. Interestingly, no obvious toxicity was observed in the heart, liver, kidney, small intestine, or stomach at dosages of up to 1800 mg/kg after treating the OVX rats for 26 weeks. XLGB was shown to be very effective in treating osteoporosis in OVX rats. No obvious toxicity or adverse effects developed in OVX rats at dosages up to 1800 mg/kg, which is equivalent to 6 times the daily-recommended dose. Therefore, XLGB should be considered a good option for the treatment of postmenopausal osteoporosis.